The Representation of Gender Inequality during the Victorian Era in “Enola Holmes: The Case of the Missing Marquess” - Saputri, Fanny Diah Eka; Rahayu, Endang Yuliani (Dinamika Bahasa dan Budaya, 2025)
This analysis discusses the types of gender inequality and representations of gender inequality and feminism as depicted in the novel “Enola Holmes: The Case of the Missing Marquess.” That occurred in the Victorian era. This study aims to find out the form of Gender Inequality experienced by Enola and how feminism is depicted in the novel “Enola Holmes: The Case of the Missing Marquess.” In this study, the writer uses a context-oriented approach. The approach applied to the study is the theory of Social Roles by Alice H. Eagly. According to this theory, the natural differences between men and women may lead to social and cultural expectations. The results of this analysis, the writer found that gender inequality that occurred in the Victorian era were in the field of stereotype, violence and subordination. In addition, a Feminism is also depicted by Enola's intelligent, independent and courageous behaviour. Therefore, Enola Holmes is described as a feminist who fights against inequality in the Victorian era. Key words: Gender Inequality, Feminism, Gender Roles